2021
DOI: 10.3389/fphar.2021.648107
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Derivative Cur20 Attenuated Cerebral Ischemic Injury by Antioxidant Effect and HIF-1α/VEGF/TFEB-Activated Angiogenesis

Abstract: In this paper, a curcumin derivative Cur20 was synthesized for better hydrolytic stability, which showed a higher angiogenic effect on zebrafish model than curcumin. In order to reveal the potential effects on neuroprotection, a mouse model of vascular dementia (VaD) induced by permanent right common carotid artery occlusion (rUCCAO) was established. After two weeks of curcumin administration, the cognitive function of mice was detected by Morris water maze and Y maze. The alteration on oxidative injuries and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…also reported that silencing FBXW7 in hypoxia reduces ubiquitinated HIF-1α levels to improve HIF-1α expression [ 13 ]. Additionally, Cur20 enhanced angiogenesis in model mice with cerebral ischemic injury by activating the HIF-1α/VEGF signaling pathway, notably attenuating cognitive dysfunction in mice [ 48 ]. As revealed by Rania G Abdel-Latif et al ., empagliflozin upregulates the expression of the HIF-1α/VEGF signaling pathway to reduce the cerebral infarction area and alleviate neuronal apoptosis and cerebral injury in I/R-injured rats [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…also reported that silencing FBXW7 in hypoxia reduces ubiquitinated HIF-1α levels to improve HIF-1α expression [ 13 ]. Additionally, Cur20 enhanced angiogenesis in model mice with cerebral ischemic injury by activating the HIF-1α/VEGF signaling pathway, notably attenuating cognitive dysfunction in mice [ 48 ]. As revealed by Rania G Abdel-Latif et al ., empagliflozin upregulates the expression of the HIF-1α/VEGF signaling pathway to reduce the cerebral infarction area and alleviate neuronal apoptosis and cerebral injury in I/R-injured rats [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 Several groups have demonstrated that CUR can inhibit cerebral ischemia. 7,[21][22][23] However, there is much that has not yet been revealed regarding the underlying mechanisms. A recent study shows that curcumin has neuroprotective effects due to its antioxidant in detail.…”
Section: Discussionmentioning
confidence: 99%
“…24 Besides antioxidant anti-inflammatory effects of CUR, Zhang et al, showed that the expression of vascular endothelial growth factor (VGEF) protecting neurons from ischemic injury and improving synaptic plasticity was increased by Cur20 which is a CUR derivate. 23 Also, it's been reported that CUR is more effective in neuroprotection, especially when applied as nanoparticles. 8,25 Experimental models of ischemia showed that the route of administration of CUR also affects its activity.…”
Section: Discussionmentioning
confidence: 99%
“…A device composed of three arms was labeled as A, B, and C. The mice were subjected to the Y-maze task. 32 Mice were first placed at the center of the maze facing arm A. When the mouse was navigating the maze, the number and the order of arm entries were recorded for 8 min.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%